Assessing Distributional and Perceived Equity of Urban Green Spaces in Qingdao’s Historic Urban Area - Naibin Jiang; Xinyu Li; Zhen Peng; Qichao Ban; Yuting Feng (Buildings, 2023)
Urban green spaces (UGSs) satisfy citizens’ physical and psychological demands and are considered an integral part of sustainable urban development. However, the distribution of UGS is often uneven, especially in historic urban areas with high building density and limited facilities, thus leading to issues of green inequity. This study examines two dimensions of green equity in Qingdao’s historic urban area, distributional equity and perceived equity, based on a fine-grained division of units and districts. Distributional equity is analyzed using the Gaussian two-step floating catchment area (G2SFCA) method and Gini coefficient to accurately calculate the equity in distribution and accessibility of UGSs. The perceived equity is assessed through the green view index (GVI) and location quotient of the streets, which represents citizens’ visual perception of green quality. Based on these analyses, a dual-perspective evaluation model of green equity is conducted, and the results show a significant imbalance of greenery supply and population demand in the historical urban area of Qingdao. This disequilibrium in green spaces leads to 62.20% of people living with low green equity, while only 8.12% experience high green equity. To maximize social justice, priority should be given to improving the 15 districts with low green equity; doing so could effectively reduce green inequity within historic urban areas where facilities and resources are relatively scarce, thereby improving the efficiency of urban renewal efforts.